Effect of native growth promoting bacteria and commercial biofertilizers on growth and yield of wheat (Triticum aestivum) and barley (Hordeum vulgare) under salinity stress conditions - Emami, Tahereh; Mirzaeiheydari, Mohammad; Maleki, Abbas; Bazgir, Masoud (Cellular and Molecular Biology, 2019)
Salinity is one of the main obstacles to the production of crops in dry regions of the world. This study focuses on the effects of different strains of plant growth promoting rhizobacteria (PGPR) isolated from native soils on the physiological responses of wheat and barley plants under normal and salt stress conditions. Soil samples were collected from a field in Ilam province, in Iran and bacterial isolates were isolated and screened for salt tolerance, included siderophore and ACC-deaminase production and phosphate solubilizing. Thereafter a two-years greenhouse experiment was conducted as a completely randomized block design with four replications. The applied treatments included bacterial inoculation at five levels (B0: non-inoculation, B1: Siderophore producing + salt-tolerant bacteria, B2: phosphate solubilizing + salt-tolerant bacteria, B3: ACC-deaminase producing + salt-tolerant bacteria, B4: Barvar-2 biological fertilizer, B5: Biofarm-2 biological fertilizer) and salt stress at three levels (S1: 0 dS/m, S2: 4 dS/m, S3: 8 dS/m). Results showed that phosphate solubilizing+ salt-tolerant bacteria resulted in the highest barley grain yield at 4 dS/m salinity level and had no significant difference with ACC-deaminase producing + salt-tolerant bacteria and Barvar-2 biological fertilizer and Biofarm-2 biological fertilizer. The highest proline content in wheat and barley observed in Siderophore producing+ salt-tolerant bacteria at 8 dS/m by 17.48 and 23.42, respectively, followed by phosphate solubilizing+ salt-tolerant bacteria by 16.53 and 19.78. Therefore, the application of isolated growth promoting bacteria can be recommended as an effective biofertilizer in Ilam province.